MATRIKS REPRESENTASI HOMOMORFISMA MODUL BEBAS - , DEWI SETYANINGSIH, Dra. Diah Junia Eksi Palupi, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modul is a set that is formed from an abelian group with a scalar multiplication of binary operation over elements of a ring with identity. In other words, a modul is a generalization of a vector space in which the scalars are elements of an arbitrary ring with identity. A modul is said to be free if it has basis. A function that preserves binary operation of a free modul is said to be a free modul homomorphism. The free modul homomorphism can be presented with a matrix over ring which is called matrix representation of free modul homomorphism. This bachelor thesis discusses about matrix over ring, modul, free modul, and some characteristics of matrix representation of free modul homomorphism that is some characteristics of the matrix that represent free modul homomorphism.